Prevalence of subclinical mastitis pathogens in small dairy farms in Republic of North Macedonia - Janevski Aleksandar; Cvetkovikj, Iskra; Kiprijanovska Sanja; Dimovski Aleksandar; Davalieva Katerina; Angjelovski Ljupco; Kjosevski MIroslav; Mitrov, Dine (Faculty of Veterinary medicine in Skopje, 2020)
Subclinical mastitis is an asymptomatic udder infection distributed worldwide with enormous losses in the dairy industry. The study’s objective was to determine the presence of this pathological condition in small dairy farms in the R. of N. Macedonia and to identify the most common associated bacteria. Milk samples were obtained from 96 dairy cows (378 udder quarters) in seven dairy farms, in 3 consecutive samplings 24-72 hours apart. The samples were cultured on routine bacteriological growth media and incubated for 24-48 hours. The isolates were identified by AximaiD Plus MALDITOF MS Platform. Subclinical mastitis was found in 49 animals (51%) and 104 infected quarters (27%). The most frequent isolated bacteria on cow level were Streptococcus uberis (19.4%), Staphylococcus haemolyticus (13.4%), Staphylococcus aureus (7.4%) and Staphylococcu ssimulans (7.4%). On quarter level, the most isolated pathogen was Streptococcus uberis (35.6%) followed by Staphylococcu shaemolyticus and Staphylococcus aureus (10.3% and 9.2% respectively). Subclinical mastitis was found to be highly present in the selected small dairy farms. The most prevalent bacteria identified in the dairy farms (Streptococcus uberis, Staphylococcus aureus and coagulase–negative staphylococci) indicate that poor management and udder health practices, inadequate milking procedures and lack of mastitis control strategies greatly contribute to occurrence and persistence of subclinical mastitis.
Keywords: subclinical mastitis, MALDI-TOF, bacteria, milk